Development of Floral Expressed Sequence Tag Resource from and Characterization of Fragrance-Related Gene Transcripts in Vanda Mimi Palmer - Teh, Seow Ling (2011)
Vanda Mimi Palmer (VMP) is a highly sought after fragrant-orchid hybrid in Malaysia. It is economically important in cosmetic and beauty industries and is also a famous potted ornamental plant. To date, no work corresponding to fragrance-related genes of vandaceous orchids has been reported and very limited molecular information on fragrance from other plants despite extensive analyses of floral fragrance or volatiles been studied. In fact, the biosynthesis pathways of flower fragrance are still incomplete. The aims of this study were to develop a floral expressed sequence tags (EST) resource, as well as to identify and characterize potential fragrance-related transcripts in this orchid hybrid. A previously constructed floral cDNA library of VMP representing transcripts of fragrance-associated genes and floral developmental genes was used to generate 2,132 ESTs. Clustering, annotation and assembling of the ESTs identified 1,196 unigenes which defined 966 singletons and 230 contigs. The VMP dbEST were functionally classified by Gene Ontology (GO) into three groups: Molecular Functions (51.2%), Cellular Component (16.4%) and Biological Processes (24.6%) while the remaining 7.8% showed no hits with GO identifier. A total of 112 EST-SSR (9.4%) was mined. Five fragrance-related transcripts were selected for full-length isolation and expression analysis using real-time quantitative RTPCR. They were acetyl-CoA acetyltransferase (VMPACA), 3-hydroxy-3-methylglutaryl-coenzyme A reductase (VMPHMGR), 1-deoxy-D-xylulose 5-phosphate synthase (VMPDXPS), linalool synthase (VMPLis) and lipoxygenase (VMPLox). Those transcripts were developmentally regulated. Three of them were highly expressed in full-bloom stage, and sepals and petals were found to be the tissues with the highest expression levels. Full-length cDNA have been obtained for two of the fragrance-related transcripts (VMPACA and VMPHMGR). Cloning and over-expression of three of the full length cDNAs [VMPACA, VMPHMGR, and a sesquiterpene synthase (VMPSTS) isolated from a previous study] were performed in Escherichia coli BL21(DE3)pLysS strain. Theexpression of those transcripts, fused to N-terminal thioredoxin (Trx·Tag), S·Tag and His·Tag fusion proteins in pET32(a), yielded recombinants VMPSTS and VMPHMGR which were only partially soluble while VMPACA was present as an insoluble protein. Functional enzymatic assays were carried out to analyse the functionality of the potential products produced from the catalytic activities of VMPSTS and VMPHMGR, respectively. VMPSTS was expressed as a functionally inactive recombinant protein with no sesquiterpene synthase compounds being detected. VMPHMGR, however, successfully catalyzed the conversion of HMG-CoA to mevalonate lactone. Dehydromevalonic lactone and pantolactone, derivatives of mevalonate lactone were detected from the catalytic reaction of VMPHMGR using GC-MS analysis. The development of a Vanda Mimi Palmer expressed sequence tags (VMPESTs) database will enhance the understanding of the molecular biology of fragrance biosynthesis pathways in vandaceous orchids and facilitate the identification of novel fragrance-related transcripts in other scented flowers. The successful expression of the cloned products may prove to be a useful asset for applications in the perfumery industry for the generation of custom-made fragrance products.